Optimization of ATSC Mobile Handheld Service Capacity. (24th March 2013) - Issa, Omneya
Abstract : Mobile TV has become a reality offered on several mobile delivery systems. Among them is the Advanced Television System Committee (ATSC) system for mobile and handheld digital television services, known as ATSC Mobile DTV or ATSC M/H, which has moved from standardization to implementation. As the North American broadcast industry is preparing to provide Mobile DTV service to consumers, this work discusses important technical parameters that affect the TV service quality and capacity. Since additional error correction mechanisms were added to overcome mobile transmission problems, the available payload for M/H services is limited. This creates a need to efficiently use the available M/H bandwidth. The paper aims to optimize the Mobile DTV service capacity while maintaining an acceptable perceived quality. It presents tradeoffs between several factors affecting service capacity and signal robustness, which is prominent for designing Mobile TV broadcasting scenarios.